Targeting menin for precision therapy in high-risk acute myeloid leukemia - Abdur Jamil; Zaheer Qureshi; Zain Mary El-amir; Gillian Kupakuwana-Suk; Hamzah Akram; Mohsin Ahmad; Eric Huselton (Leukemia Research Reports)
Objective: This mini-review provides an overview of the current evidence for Revumenib, a first-in-class menin inhibitor, in treating AML with KMT2A rearrangements or NPM1 mutations. This therapy represents a promising advancement by selectively disrupting leukemogenic pathways. Summary: The clinical promise of Revumenib in genetically defined AML highlights its potential role in shaping the future treatment landscape. This mini-review underscores the need for ongoing trials to define optimal dosing, safety protocols, and combination therapies, with the ultimate goal of establishing Revumenib as a standard of care for high-risk AML subsets.